2019
DOI: 10.1542/hpeds.2018-0225
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Screening in Mothers and Infants Exposed to Opioids

Abstract: Hepatitis C virus (HCV) is the most common blood-borne pathogen in the United States. In the context of the opioid epidemic, there has been a dramatic rise in perinatal opioid use and the prevalence of HCV infection, which can be transmitted to infants. One national guideline recommends HCV screening for all pregnant women and screening for HCV-exposed newborns after 18 months of age. In this study, we aimed to identify the trends in HCV prevalence and screening among mothers using opioids during pregnancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Despite growing knowledge regarding the risks of perinatal transmission, the true burden of perinatally acquired HCV remains unknown. There are clear guidelines from the IDSA/AASLD recommending that HCV-exposed infants receive an HCV antibody test after 18 months of age or HCV RNA test after 2 months old [ 36 ]; however, multiple studies evaluating healthcare utilization have shown that HCV-exposed infants are not routinely linked to testing for HCV [ 18 , 37 – 42 ]. For example, a recent study from a large health center estimated that at least two-thirds of perinatally acquired HCV cases were missed due to lack of recognition of risk factors and inconsistencies in documenting maternal infection in the child’s medical record [ 37 ].…”
Section: Perinatal Transmission and Significance For Pediatric Popula...mentioning
confidence: 99%
“…Despite growing knowledge regarding the risks of perinatal transmission, the true burden of perinatally acquired HCV remains unknown. There are clear guidelines from the IDSA/AASLD recommending that HCV-exposed infants receive an HCV antibody test after 18 months of age or HCV RNA test after 2 months old [ 36 ]; however, multiple studies evaluating healthcare utilization have shown that HCV-exposed infants are not routinely linked to testing for HCV [ 18 , 37 – 42 ]. For example, a recent study from a large health center estimated that at least two-thirds of perinatally acquired HCV cases were missed due to lack of recognition of risk factors and inconsistencies in documenting maternal infection in the child’s medical record [ 37 ].…”
Section: Perinatal Transmission and Significance For Pediatric Popula...mentioning
confidence: 99%
“…[16][17][18] This creates a gap in timing from diagnosis to treatment and increases the potential of HCV-positive patients and their infants being lost to follow-up. 6,16 Previous studies in Maine used Medicaid claims data 19 and electronic medical record (EMR) and Health Info Net (a large nonprofit interpractice system database for record sharing) 10 to track pregnant people with OUD; however, tracking follow-up care for mother-infant dyads was suboptimal. 10 Separate postpartum and pediatric care, loss of health insurance after delivery, complex substance use and mental health disorders, and variations in legal custody of the infant result in fragmented care delivery and inadequate follow-up.…”
mentioning
confidence: 99%
“…6,16 Previous studies in Maine used Medicaid claims data 19 and electronic medical record (EMR) and Health Info Net (a large nonprofit interpractice system database for record sharing) 10 to track pregnant people with OUD; however, tracking follow-up care for mother-infant dyads was suboptimal. 10 Separate postpartum and pediatric care, loss of health insurance after delivery, complex substance use and mental health disorders, and variations in legal custody of the infant result in fragmented care delivery and inadequate follow-up. 10 There are few examples of effective approaches to tracking HCV follow-up and treatment outcomes for perinatal patients and their infants across a wide service area.…”
mentioning
confidence: 99%
See 2 more Smart Citations